Oxford studies in philosophy of law volume 4 - Gardner, John; Green, Leslie; Leiter, Brian (Oxford University Press, 2021)
This volume provides a forum for some of the best new philosophical work on law, by both senior and junior scholars from around the world. The chapters range widely over issues in general jurisprudence (the nature of law, adjudication, and legal reasoning); the philosophical foundations of specific areas of law (from criminal law to evidence to international law); the history of legal philosophy; and related philosophical topics that illuminate the problems of legal theory"--